The Coping Circumplex Model: An Integrative Model of the Structure of Coping With Stress - Stanisławski, Krzysztof (Frontiers in Psychology, 2019)
It seems obvious that the identification of coping structure is necessary to understand how stress affects human health and functioning. Despite numerous coping conceptualization proposals, there is no agreement as to the core coping categories. This article presents the Coping Circumplex Model (CCM), which is designed to integrate various coping distinctions, drawing inspiration from the tradition of circumplex models in psychology. The model is based on the assumption that individuals in stressful situations face two tasks: they need to solve the problem and regulate their emotions, which are reflected in two corresponding dimensions, that is, the problem coping dimension and emotion coping dimension. Problem coping and emotion coping are interpreted as bipolar dimensions. Importantly, these dimensions define a space for other coping categories. The model contains a total of eight coping styles forming a circumplex: positive emotional coping, efficiency, problem solving, preoccupation with the problem, negative emotional coping, helplessness, problem avoidance, and hedonic disengagement. The paper discusses the potential of the CCM to overcome some of the problems of stress psychology by: (a) supplementing the set of coping categories (i.e., process, strategy, style) with coping mode; (b) providing a foundation for the integration of numerous coping constructs; (c) enabling the interpretation of results obtained by means of different coping measures, thus facilitating knowledge consolidation; (d) explaining relationships between coping and adjustment after trauma, as well as explaining the mechanisms of psychological interventions (e.g., cognitive therapy, exposure therapy); (e) clarifying liknages between the effectiveness of coping strategies and situation controllability. Moreover, the CCM may elucidate the relationship between coping and emotion regulation (e.g., cognitive reappraisal and expressive suppression).